The impact of imposing implicit auction of cross border capacities on the amount of emissions in Czech Republic, Slovakia and Hungary. - Mráz, Vít (2017)
One of the pieces of further interconnecting European power markets is market coupling, or more specifically implicit auction of cross border transmission capacities. That should lead to more effective allocation of resources and, according to hypothesis, surprisingly to slightly higher emission of some pollutants per generated unit of electricity into the air. Purpose of this thesis is to verify if this really happened in Czech Republic, Slovakia and Hungary. In order to describe this mechanism merit order curve is constructed and day ahead hourly prices of electricity are used. From these approximate generation from coal and gas power plants are calculated and finally out of that total amount of pollutants emitted into the air before and after market coupling is calculated. Results confirms hypothesis in Czech Republic and Hungary, but causality is questionable.